2024
DOI: 10.1038/s41598-024-58009-7
|View full text |Cite
|
Sign up to set email alerts
|

Research on the effect of different aerobic activity on physical fitness and executive function in primary school students

Yue Ren,
Jun Chu,
Zhongyuan Zhang
et al.

Abstract: To evaluate the effect of 16 weeks of different aerobic activity on physical fitness and executive functions in primary school students. 90 right-handed students from China (Boys = 46; Girls = 44) participated in our study and were randomly separated into four groups: 20 in the control group (Con), 23 in the physical activity group (PA), 25 in the intellectual activity group (IA), 22 in the physical activity and intellectual activity group (PA + IA). The students in PA, IA and PA + IA group received aerobic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Huhtiniemi and colleagues (2023) have shown that if physical fitness exercises are consistently integrated into school programs, all indicators of health-related physical fitness improve [ 8 ]. And, of course, regular weekly exercise helps to increase the level of physical fitness, especially just muscle strength and cardiorespiratory endurance [ 6 ]. And, physical fitness, in turn, is related to cognitive function and working memory [ 7 ] and also generally to academic success and quality of life [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huhtiniemi and colleagues (2023) have shown that if physical fitness exercises are consistently integrated into school programs, all indicators of health-related physical fitness improve [ 8 ]. And, of course, regular weekly exercise helps to increase the level of physical fitness, especially just muscle strength and cardiorespiratory endurance [ 6 ]. And, physical fitness, in turn, is related to cognitive function and working memory [ 7 ] and also generally to academic success and quality of life [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that to improve physical fitness, children aged 5–17 must engage in moderate to vigorous physical activities, as recommended by the WHO [ 5 ]. Both regular weekly training [ 6 , 7 ] and short, intense exercises during school [ 8 ] contribute to the development of strength and endurance.…”
Section: Introductionmentioning
confidence: 99%